How will Basel II affect bank lending to emerging markets? An analysis based on German bank level data - Thilo Liebig; Daniel Porath; Beatrice Weder di Mauro; Michael Wedow (Deutsche Bundesbank, 2004)
This paper investigates whether the new Basel Accord will induce a change in bank lending to emerging markets using a comprehensive new data set on German banks' foreign exposure. We test two interlinked hypotheses on the conditions under which the change in the regulatory capital would leave lending flows unaffected. This would be the case if (i) the new regulatory capital requirement remains below the economic capital and (ii) banks' economic capital to emerging markets already adequately reflects risk. On both accounts the evidence indicates that the new Basel Accord should have a limited effect on lending to emerging markets.
Keywords: F33; G28; F34; 330; Basel Accord; Banking Regulation; International Lending; Internationale Kreditvergabe; Kreditgeschäft; Deutsch; Eigenkapitalvorschriften; Basel II; Schwellenländer